2016
DOI: 10.1016/j.amjcard.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anesthesia Type on Outcomes of Transcatheter Aortic Valve Implantation (from the Multicenter ADVANCE Study)

Abstract: Transcatheter aortic valve implantation (TAVI) has become the standard of care for many patients with symptomatic severe aortic stenosis who are at increased risk of morbidity and mortality during surgical aortic valve replacement. However, there is still no general consensus regarding the use of general anesthesia (GA) versus local anesthesia with sedation (non-GA) during the TAVI procedure. Using propensity score matching analysis, we analyzed the characteristics and outcomes of patients undergoing TAVI with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 14 publications
5
57
1
2
Order By: Relevance
“…Similar to our report, in Transcatheter Valve Treatment Sentinel (TCVT) registry, the patients in the non-GA group were older, and the rate of previous coronary artery bypass grafting (CABG) surgery was higher in the GA group, whereas in contrast to our study they observed no difference in the BMI, left ventricular ejection fraction and eGFR between the GA and non-GA groups 4 16. In keeping with our report, there were higher rate of patients with previous CABG and impaired left ventricular function in the GA group in ADVANCE registry 14. A higher logistic EuroSCORE was observed in the GA cases in the ADVANCE, Italian CoreValve and TCVT registries but not in the French Aortic National CoreValve and Edwards 2 (FRANCE 2) registry.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our report, in Transcatheter Valve Treatment Sentinel (TCVT) registry, the patients in the non-GA group were older, and the rate of previous coronary artery bypass grafting (CABG) surgery was higher in the GA group, whereas in contrast to our study they observed no difference in the BMI, left ventricular ejection fraction and eGFR between the GA and non-GA groups 4 16. In keeping with our report, there were higher rate of patients with previous CABG and impaired left ventricular function in the GA group in ADVANCE registry 14. A higher logistic EuroSCORE was observed in the GA cases in the ADVANCE, Italian CoreValve and TCVT registries but not in the French Aortic National CoreValve and Edwards 2 (FRANCE 2) registry.…”
Section: Discussionsupporting
confidence: 88%
“…Acute kidney injury stage III and bleeding, even after propensity score matching, was higher in the GA patients in the Italian CoreValve registry 15. The report from the TCVT registry also showed a higher rate of renal replacement therapy in the GA TAVI group,4 and there was a higher rate of vascular complications in the non-GA TAVI cohort in the ADVANCE registry 14…”
Section: Discussionmentioning
confidence: 89%
“…We reviewed 35 full-text articles and identified 20 articles for inclusion in our review (figure 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] All the studies were observational studies except one RCT. 32 Table 1 shows the baseline clinical characteristics of the included studies.…”
Section: Study Selection and Eligibility Criteriamentioning
confidence: 99%
“…Anesthetic agents, such as fentanyl, propofol, dexmedetomidine, and midazolam, have never been reported to influence blood platelets. Recent data, using propensity score-matching analysis, showed less procedural duration, less fluoroscopic time, and more postprocedural complications in a non-GA cohort [17,18]. Longer X-ray exposure, longer procedural time, and larger contrast amounts have been reported to be associated with TP, which might help to elucidate this correlation between TP and anesthesia techniques [9].…”
Section: Discussionmentioning
confidence: 99%